Thermal desiccation of geosynthetic clay liners under brine pond conditions. Issue 6 (5th December 2020) - Ghavam-Nasiri, A.; El-Zein, A.; Airey, D.; Rowe, R. K.; Bouazza, A.
Abstract : Desiccation of geosynthetic clay liners (GCLs) in composite lining systems is investigated experimentally. Field conditions similar to those encountered in brine ponds (high surface temperature and low overburden pressure of 20 kPa) are simulated in two soil columns. The GCL is first allowed to hydrate from a sandy subsoil under isothermal conditions (44 days), then subjected to a thermal gradient applied through a heat source (78°C) on top of the geomembrane (39 days). Changes in water content, temperature of subsoil and movement of the surface during hydration and heating stages are measured. A sharp rise in moisture content is observed in the upper region of the subsoil immediately after the start of heating, which shortly dissipates. After 39 days of heating, the bentonite in the tested GCLs is dehydrated to around 8% gravimetric water content, down from over 100% after hydration. In addition, more than 3 mm of shrinkage of bentonite in the vertical direction is recorded. X-ray imaging after the tests reveals extensive desiccation cracking of bentonite. The study has confirmed the existence of a significant risk of desiccation of GCLs under thermal gradients and has generated data that are useful for validating models used for the prediction of GCL behaviour.